Expression, Proliferation and Apoptosis of miR‑92b in Oral Squamous Cell Carcinoma - Yongzhi XU; Fang FANG; Jinghui WANG; Chunli ZHAO; Jingyang ZHAO; Peng DING (Tehran University of Medical Sciences, 2020)
Background: Expression of miR‑92b in oral squamous cell carcinoma (OSCC) rat tissue and its effect on the OSCC CAL‑27 cells were investigated. Methods: The study was performed in Qingdao Stomatological Hospital, Qingdao, China on December 2018. Thirty Wistar rats were used to construct models of oral squamous cell carcinoma. CAL‑27 cells trascfected by Lipofectamine 2000 were divided into miR‑92b inhibitor, miR‑NC and blank groups. RT‑qPCR was used for the detection of the expression level of miR‑92b, and MTT and flow cytometry were carried out for the detection of the effect of miR‑92b on the proliferation and apoptosis of CAL‑27 cells, respectively. Results: The expression level of miR‑92b was significantly higher in tumor tissues than that in normal tissues (P<0.001). The miR‑92b inhibitor group had significantly lower proliferation ability but higher apoptosis rate of CAL‑27 cells than the miR‑NC and blank groups. After miR‑92b was downregulated by trans-fecting cells, the expression level of miR‑92b was significantly lower in the miR‑92b inhibitor group than that in the miR‑NC and blank groups. Conclusion: miR‑92b inhibitor can inhibit the proliferation of CAL‑27 cells and promote apoptosis, which provides certain references for clinical treatment. It is expected to be a potential target for treating OSCC.